STUDENTS’ PERCEPTIONS ON WATCHING KOREAN VARIETY SHOW WITH ENGLISH SUBTITLE IN LEARNING VOCABULARY - Nurdin, Rifqah Nur' Arfani; Talib, Ahmad; Radhiyani, Fitri (JTechLP: Journal of Technology in Language Pedagogy, 2024)
This research aims to determine students’ perceptions of watching Korean variety shows with English subtitles in learning vocabulary. This research applied descriptive qualitative research design. The instrument used in this research is interviews. The participants of this research were seven students from Universitas Negeri Makassar who were determined using a purposive sampling technique. The participants were all English education students and had experienced watching Korean variety shows with English subtitles in learning vocabulary. The results of the research proved how a person's perception is formed based on three perception indicators: absorption of the stimuli, understanding of the stimuli, and assessment/ evaluation.